New-onset super-refractory status epilepticus: A case series of 26 patients. (20th October 2020) - Matthews, Elizabeth; Alkhachroum, Ayham; Massad, Nina; Letchinger, Riva; Doyle, Kevin; Claassen, Jan; Thakur, Kiran T.
Abstract : Objective: To better understand the heterogeneous population of patients with new-onset refractory status epilepticus (NORSE), we studied the most severe cases in patients who presented with new-onset super-refractory status epilepticus (NOSRSE). Methods: We report a retrospective case series of 26 adults admitted to the Columbia University Irving Medical Center neurologic intensive care unit (NICU) from February 2009 to February 2016 with NOSRSE. We evaluated demographics, diagnostic studies, and treatment course. Outcomes were modified Rankin Scale score (mRS) at hospital discharge and most recent follow-up visit (minimum of 2 months post discharge), NICU and hospital length of stay, and long-term antiepileptic drug use. Results: Of the 252 patients with refractory status epilepticus, 27/252 had NORSE and 26/27 of those had NOSRSE. Age was bimodally distributed with peaks at 27 and 63 years. The majority (96%) had an infectious or psychiatric prodrome. Etiology was cryptogenic in 73%, autoimmune in 19%, and infectious in 8%. Seven patients (27%) underwent brain biopsy, autopsy, or both; 3 (12%) were diagnostic (herpes simplex encephalitis, candida encephalitis, and acute demyelinating encephalomyelitis). On discharge, 6 patients (23%) had good or fair outcome (mRS 0–3). Of the patients with long-term follow-up data (median 9 months, interquartile range 2–22 months), 12 patients (71%) had mRS 0–3. Conclusion: Among our cohort, nearly all patients with NORSE had NOSRSE. The majority were cryptogenic with few antibody-positive cases identified. Neuropathology was diagnostic in 12% of cases. Although only 23% of patients had good or fair outcome on discharge, 71% met these criteria at follow-up.